ANALYSING THE USE OF BLOGSPOT IN ONLINE LEARNING: A STUDY OF EFFECTIVENESS AND CONSTRAINTS - Auliah, Army; Febrianti, Andi Evi; Syahrir, Muhammad; Cahyani, Vika Puji (Jurnal IPA Terpadu, 2024)
Blogspot in this literature study is a type of online learning hybrid used as an online learning instrument. This literature review allowed the researcher to review previous studies on the use of technology in education, particularly Blogspot. The use of blogspot had a positive impact on student engagement and facilitated a deeper understanding of concepts. The stages carried out in this research are Problem Identification and Research Objectives, Literature Data Collection, Literature Data Analysis, Synthesis of Findings and Reporting of Research Results. Based on the results of the literature study, blogspot is proven to be effective in supporting flexible learning, especially in collaborative activities, writing, and project-based learning. Its features allow students to access materials easily and engage in online discussions. Despite several advantages, there are significant constraints in using Blogspot. One major challenge is Blogspot’s limited class management and evaluation features compared to other Learning Management Systems (LMS). Actionable recommendations from the findings are to combine Blogspot with LMS platforms for a better learning experience and provide targeted digital literacy training. With these recommendations, educators and institutions can consider Blogspot for online learning.